A First Look at the Acquisition and Appraisal of the 2010 Olympic and Paralympic Winter Games Fonds: or, SELECT * FROM VANOC _Records AS Archives WHERE Value=“true”; - Mumma, Courtney C.; Dingwall, Glenn; Bigelow, Sue (Archivaria, 2011)
Since 2008, the City of Vancouver Archives has been working to develop a digital archives. Much of the funding and accompanying urgency were linked to the City’s obligation to preserve the records of the Organizing Committee for the 2010 Olympic and Paralympic Winter Games (VANOC). This paper describes some of the difficulties encountered in acquiring VANOC’s digital records and the Archives’ struggles to map the different tasks involved in acquisition and appraisal against the digital processing workflow, which is constrained by the technology used, and therefore less flexible than for analogue records. Complexities are due both to the records creator’s technical environment as well as limitations imposed by the Archives’ digital preservation solution. The paper also considers some of the ways in which these core archival activities may diverge from long-established practices when moving into the digital environment. RÉSUMÉ Les Archives de la ville de Vancouver travaillent depuis 2008 à développer des archives numériques. La plus grande partie du financement et le sentiment d’urgence face à ce projet furent liés à l’obligation de la ville de préserver les documents du Comité d’organisation des Jeux olympiques d’hiver de 2010 (COVAN). Ce texte décrit quelques-unes des difficultés rencontrées à l’acquisition des documents numériques du COVAN. Il documente aussi les efforts des Archives pour faire correspondre les différentes tâches liées à l’acquisition et à l’évaluation du processus de travail relié au traitement des documents numériques, qui est limité par les technologies utilisées et donc moins flexible que pour les documents analogues. Les complexités sont dues à la fois à l’environnement technique utilisé par les créateurs des documents et aux limites imposées par la solution de préservation numérique des Archives. Ce texte examine aussi certaines façons dont les activités archivistiques de base peuvent différer des pratiques bien établies quand on les transpose dans un environnement numérique.